Risk Communication Practices in The 7 Summit Wonosobo Trail Run: A Case Study of The Sobat Tektok Community - Puji Mohamad Zulfiki; Yulia Rahmawati; Wininda Qusnul Khotimah (Informasi, 2026)
The rapid growth of trail running in Indonesia has not been followed by a proportional increase in safety literacy, resulting in an escalation of fatal mountain incidents caused by the runner’s optimism bias and competitive ego. This study examines how the Sobat Tektok (SOTEK) community designs and executes risk mitigation communication for the extreme 7 Summit Wonosobo 2025 event. Employing a qualitative descriptive case study, data were collected through in-depth interviews with five core informants, digital field observations within community WhatsApp groups, and a comprehensive standard operating procedure (SOP) document analysis. Grounded in Peter Sandman’s Risk Communication Theory and the Social Amplification of Risk Framework (SARF), the results reveal that SOTEK successfully integrated rigid pre-event screening and data-driven technical message visualization on digital media platforms to deconstruct individual cognitive distortions. During live field execution, communication dynamically shifted from top-down authoritative broadcasting to an adaptive, decentralized, peer-supported dialogue led by field sweepers. This empathetic field interaction effectively dismantled individual athletic arrogance, allowing exhausted or gear-deficient runners to execute rational, self-selected "Did Not Finish" (DNF) choices. Consequently, this collective, culture-centered communication system transformed regulatory constraints into life-saving parameters, culminating in an impeccable zero-casualty and zero-accident record.